Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1002/jhet.5570180541
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some 1‐substituted‐3‐or‐5‐styrylpyrazoles

Abstract: The synthesis of the title compounds by the Wittig‐Horner reaction is described, using the 3‐or‐5‐hydroxymethylpyrazole derivatives as precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Deshayes et al reported the reaction of phosponic esters, prepared from 1-substituted 5-bromomethylpyrazoles 105 and triethyl phosphite, with substituted benzaldehydes and furfural, in dimethoxyethane, as a method to prepare ( E )-4-ethoxycarbonyl-3-methyl-5-styryl-l-substituted pyrazoles 106 ( Scheme 32 ) [ 75 , 85 ].…”
Section: Synthesis Of Styrylpyrazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Deshayes et al reported the reaction of phosponic esters, prepared from 1-substituted 5-bromomethylpyrazoles 105 and triethyl phosphite, with substituted benzaldehydes and furfural, in dimethoxyethane, as a method to prepare ( E )-4-ethoxycarbonyl-3-methyl-5-styryl-l-substituted pyrazoles 106 ( Scheme 32 ) [ 75 , 85 ].…”
Section: Synthesis Of Styrylpyrazolesmentioning
confidence: 99%
“…Molecules 2020, 25, x FOR PEER REVIEWDeshayes et al reported the use of 3-bromomethylpyrazole 54 as template for the synthesis of (E)-3-styrylpyrazole 55. In a first step, this compound was treated with triethyl phosphite, in the Arbusov reaction, affording the corresponding diethylphosphonomethylpyrazole, which then reacted with benzaldehyde in the presence of sodium hydride to give the corresponding (E)-3-styrylpyrazole 55 (Scheme 15)[75].Molecules 2020, 25, x FOR PEER REVIEW 13 of Synthesis of (E)-3-styrylpyrazole 55[75].…”
mentioning
confidence: 99%